Interplay between DNA replication, transcription and repair - Trautinger, Brigitte W. (2002)
The Ruv ABC and RecBCD protein complexes together can collapse and repair arrested replication forks. With their help a fork structure can be re-established on which replication can be restarted. ruv and recB mutants are therefore quite sensitive to UV light. Their survival is greatly decreased in the absence of the signalling molecules (p)ppGpp and increased when excess (p)ppGpp is present. (p)ppGpp are the effector molecules of the stringent response, regulating adaptation to starvation and other stressful environmental changes. Absence of (p)ppGpp can be compensated for by mutations in RNA polymerase that are called stringent mutations. Some of those, called rpo *, also - like excess (p)ppGpp - increase the survival of UV irradiated ruv and recB cells. A model proposed by McGlynn and Lloyd (Cell, Vol. 101, pp35-45, March 31, 2000) suggests that this is achieved by modulation of RNA polymerase, which decreases the incidence of replication fork blocks. In this work twenty-seven rpo * mutants were isolated, sequenced and mapped on the 3D structure of Thermus aquatic us RNA polymerase. I have found mutants in the ~ and ~' subunits of RNA polymerase. They lie mostly on the inner surface of the protein, well placed to make contact with the DNA substrate or the RNA product. A large number of rifampicin resistant mutations among rpo* mutations is explained by an overlap between the so-called Rif pocket and the "rpo* pocket". rpo * mutations, like stringent mutations, lead to a decrease in cell size, suppress filamentation and increase viability. For in vitro studies I purified wild type and two mutant RNA polymerases with help of a his-tagged a subunit. The experiments confirmed that rpo* mutant RNA polymerases form less stable open complexes than wild type, just like previously investigated stringent RNA polymerases. In addition I have shown here that (p)ppGpp leads to the destabilisation of RNA polymerase complexes stalled by nucleotide starvation or UV-induced lesions, though there is as yet no indication that rpo * mutations act in the same way.